2021
DOI: 10.1108/jbim-08-2020-0381
|View full text |Cite
|
Sign up to set email alerts
|

Driving forces of repurchasing social enterprise products

Abstract: Purpose This paper aims to use utilitarian benefits, hedonic benefits and corporate social responsibility to influence the consumer’s sense of brand identity and brand trust in social enterprise products and, thus, favourably affect repurchase intention. Design/methodology/approach This study dispatched 430 questionnaires in Taiwan. The top six social enterprises in the organic food industry in Taiwan that accounted for 84.0% of total green organic stores and they were selected for field investigation. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 72 publications
2
7
0
Order By: Relevance
“…Sports-venue-related research shows that consumers are sensitive to the social responsibility of commercial ice rink operators, and the positive effects such as public welfare and humanistic values the operators bring to surrounding communities impact consumers’ perceived social value [ 19 ]. Wu et al [ 20 ] recently indicated that corporate social responsibility has a largely positive effect going through brand identity and brand trust, and then affecting the decision to repurchase. Consequently, consumers’ satisfaction with a company increases when they perceive that it has fulfilled its social responsibilities, which translates into repurchase intention [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Sports-venue-related research shows that consumers are sensitive to the social responsibility of commercial ice rink operators, and the positive effects such as public welfare and humanistic values the operators bring to surrounding communities impact consumers’ perceived social value [ 19 ]. Wu et al [ 20 ] recently indicated that corporate social responsibility has a largely positive effect going through brand identity and brand trust, and then affecting the decision to repurchase. Consequently, consumers’ satisfaction with a company increases when they perceive that it has fulfilled its social responsibilities, which translates into repurchase intention [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…The last loyalty indicator analyzed is price tolerance, since those customers who are more satisfied will be willing to pay more for that product or service (Saldivar and Zolfagharian, 2022). This behavioral intention is of particular interest in the field of SEs, since consumers have the perception that prices are higher than those of conventional companies (Wu et al, 2022). In short, the satisfied customer will be willing to pay a little more, to give up looking for bargains, or to give up buying from conventional companies whose prices are usually lower.…”
Section: Loyalty Indicators As Consequences Of Customer Satisfactionmentioning
confidence: 99%
“…However, building trust is critical. While greenwashing (Chen et al, 2019) and green perceived risk (Pahlevi & Suhartanto, 2020) hurt trust, several positive antecedents are identified, including price fairness (Wang & Tsai, 2014), green perceived value (Pahlevi & Suhartanto, 2020), perceived quality (Tian et al, 2022), utilitarian benefits (Wu et al, 2022), and satisfaction (Kang & Hur, 2012;Suhartanto et al, 2021).…”
Section: Trustmentioning
confidence: 99%